Perlindungan Anak Dalam Sistem Peradilan Pidana Anak - Alvin Ferdiansya; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Child protection within the juvenile justice system is essential for safeguarding children's rights and ensuring justice. Children, as distinct from adults, require specialized treatment in legal proceedings, emphasizing rehabilitation over punishment. In Indonesia, child protection in the juvenile justice system is governed by Law No. 11 of 2012 on the Juvenile Criminal Justice System, which prioritizes the best interests of the child and supports restorative justice approaches. However, the practical implementation of these principles remains challenging due to insufficient understanding and application by law enforcement agencies, the judiciary, and other relevant institutions. This paper examines the legal framework for child protection in Indonesia’s juvenile justice system, highlighting the procedures, treatment, and safeguards in place for children in conflict with the law. It also addresses the obstacles in ensuring a justice system that fully upholds the rights and well-being of children. By exploring these issues, the study aims to offer recommendations for improving the system, ensuring that children's rights are adequately protected and that the approach to juvenile justice remains rehabilitative and restorative.